Wfs1-deficient mice display altered function of serotonergic system and increased behavioral response to antidepressants - Visnapuu, Tanel; Raud, Sirli; Loomets, Maarja; Reimets, Riin; Sütt, Silva; Luuk, Hendrik; Plaas, Mario; Kõks, Sulev; Volke, Vallo; Alttoa, Aet; Harro, Jaanus; Vasar, Eero (Frontiers in Neuroscience, 2013)
It has been shown that mutations in the WFS1 gene make humans more susceptible to mood disorders. Besides that, mood disorders are associated with alterations in the activity of serotonergic and noradrenergic systems. Therefore, in this study, the effects of imipramine, an inhibitor of serotonin (5-HT) and noradrenaline (NA) reuptake, and paroxetine, a selective inhibitor of 5-HT reuptake, were studied in tests of behavioural despair. The tail suspension test (TST) and forced swimming test (FST) were performed in Wfs1-deficient mice. Simultaneously, gene expression and monoamine metabolism studies were conducted to evaluate changes in 5-HT- and NA-ergic systems of Wfs1-deficient mice. The basal immobility time of Wfs1-deficient mice in TST and FST did not differ from that of their wild-type littermates. However, a significant reduction of immobility time in response to lower doses of imipramine and paroxetine was observed in homozygous Wfs1-deficient mice, but not in their wild-type littermates. In gene expression studies, the levels of 5-HT transporter (SERT) were significantly reduced in the pons of homozygous animals. Monoamine metabolism was assayed separately in the dorsal and ventral striatum of naive mice and mice exposed for 30 minutes to brightly lit motility boxes. We found that this aversive challenge caused a significant increase in the levels of 5-HT and 5-hydroxyindoleacetic acid (5-HIAA), a metabolite of 5-HT, in the ventral and dorsal striatum of wild-type mice, but not in their homozygous littermates. Taken together, the blunted 5-HT metabolism and reduced levels of SERT are a likely reason for the elevated sensitivity of these mice to the action of imipramine and paroxetine. These changes in the pharmacological and neurochemical phenotype of Wfs1-deficient mice may help to explain the increased susceptibility of Wolfram syndrome patients to depressive states.